Pulling your own strings - "Dyer, Wayne W." (London, 2004)
Does your family treat you like an unpaid servant? Are you afraid to stand up for yourself at work? Do you give in to pressure from friends? Do you torture yourself with guilt and remorse? If you feel and act like a victim, your life is not really your own. But if you learn to take control over your fears, weaknesses and negative feelings, then it is possible to achieve freedom - and the priceless benefits it brings. In this classic self-help book, Dr Dyer shows you in his wise and helpful way how you can take control of your own life and become a stronger person. Reading it is the first step towards a new, effective, assertive you.
Keywords: Philosophy